2020
DOI: 10.1109/access.2020.3021208
|View full text |Cite
|
Sign up to set email alerts
|

Where Do Pedestrians Look When Crossing? A State of the Art of the Eye-Tracking Studies

Abstract: It has been widely shown in the literature that analysing eye movements and positions can provide useful information for a better understanding of human perception and cognition. The eye-tracking technology, as a process of measuring where people look, has established itself as a widespread means of studying visual information processing in several domains, including in the study of human walking. Streetcrossing can be defined as a particular form of walking. Indeed, several elements have to be considered in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Our study has some notable limitations. While we contrasted time-to-arrival estimates for different gaze locations that have previously been found to be frequently sampled by pedestrians (Lévêque et al, 2020) While limiting our ability to monitor gaze and precisely control response latencies, the use of an online experiment procedure enabled us to test time-to-arrival perception in a relatively large and diverse sample (here specifically in terms of age). The convergence of our results with classical laboratory studies indicates good validity, suggesting that similar online experiments could be a suitable approach to test the role of gaze in different road traffic scenarios.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study has some notable limitations. While we contrasted time-to-arrival estimates for different gaze locations that have previously been found to be frequently sampled by pedestrians (Lévêque et al, 2020) While limiting our ability to monitor gaze and precisely control response latencies, the use of an online experiment procedure enabled us to test time-to-arrival perception in a relatively large and diverse sample (here specifically in terms of age). The convergence of our results with classical laboratory studies indicates good validity, suggesting that similar online experiments could be a suitable approach to test the role of gaze in different road traffic scenarios.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, even the minute eye movements performed spontaneously influence the perception of relevant motion parameters such as the time-toarrival of an approaching vehicle (Sudkamp, Bocian & Souto, in press). Eye tracking studies investigating gaze behavior in road-crossing demonstrate that visual exploration varies with individual factors of a pedestrian (e.g., age) and the visual composition of the road environment (e.g., type of intersection; see Lévêque, Ranchet, Deniel, Bornard & Bellet, 2020 for a review). Yet, little focus has so far been given to the question of how visual exploration affects pedestrians' motion perception in road-crossing.…”
Section: Introductionmentioning
confidence: 99%
“…The visual behavior of pedestrians in a street crossing situation is influenced by the concrete layout of the street [13,41], but also to a large extent by the existence of the time pressure [48,2]. Due to its importance to traffic safety, pedestrian attention has been studied extensively in human science [2,14,20,61].…”
Section: Introductionmentioning
confidence: 99%
“…The Fatality Analysis Reporting System of the National Highway Traffic Safety Administration, NHTSA (2017) , revealed that more than 25% of pedestrians’ fatal crashes were caused by a lack of communication and mistaken assumptions about others’ actions. Street-crossing situations involve a complex decision-making process based on several factors ( Lévêque et al, 2020 ). In this context, and especially when ambiguities remain regarding priority rules (i.e., non-signalized crossing), pedestrians and car drivers tend to interact using non-verbal communication (e.g., facial expressions, eye contacts, gestures, and body movements) in order to clarify their intentions.…”
Section: Introductionmentioning
confidence: 99%